Remarks at the G20 International Tax Symposium - Fiscal Policies to Integrate Climate and Development - Malpass, David (World Bank, Washington, DC, 2021)
World Bank Group President David Malpass remarked that the pandemic added further to the development gap, with many developing countries also suffer from fragility, human rights violations, food insecurity, lack of transparency, weak currencies, inflation, and the unfunded requirements of climate change. He highlighted that the developing world faces particular fiscal and financial challenges with the adoption by many countries of the goal of net-zero emissions. He addressed three related issues: 1) the need for a more integrated approach to climate and development; 2) the need for balanced incentive structures; and 3) the need for more support from the G20 for the world’s poorest economies, especially through the ongoing IDA20 replenishment.